The Contextualization Of The Māqāṣid Al-Syarīah Jasser Auda Theory In The Concept And Practice Of Islamic Family Law - Soni Zakaria (Al-'Adl, 2021)
This study aims to explain how the contextualization of Jasser Auda's māqāṣid āl-šyāriāh theory is used in the Islamic family law paradigm approach. This issue is important to be discussed for some reasons. First, the approach used in the paradigm of Islamic family law in Indonesia is still not based on maqasid. Second, the concept of maqashid al-syariah has a major contribution to develop the paradigm of Islamic law, including in the field of Islamic family law. Third, the concept of maqashid Auda refreshes the discourse of renewing approaches in Islamic family law. This study uses a qualitative approach with implementing a combination study, which is a combination of literature review and social contextualization. The findings showed that the concept of māqāṣid āl-šyāriāh Jasser Auda contributed greatly to the development of a paradigm in the Islamic family law study approach. The concept of māqāṣid āl-šyāriāh Jasser Auda emphasizes the value of guarding and protection towards development and rights, thus family law which has been oriented towards safeguards, can be changed towards family development. Furthermore, Auda’s philosophy system approach can be used as an alternative approach in the study of family law. The implication is that the approach offered by Jasser Auda in family law will be in line with the achievement of the Human Development Index indicators in the United Nations Development Program (UNDP).